How Does the Stock Market Development React to Energy Consumption? Evidence from the ARDL Panel Approach - Derouez Faten; Alharbi Farea; Mathlouthi Naim; Ifa Adel; Ahmed Nazar; Alrawad Mahmaod (ECONOMICS)
This article examines the relationship between stock market development and energy consumption in the Gulf Cooperation Council (GCC) countries using panel data from 1971-2021 and ARDL panel and cross-section techniques. The long-term results show that market capitalization has a significant effect on oil consumption. In contrast, the value of shares traded positively and significantly influences the consumption of oil and electricity. Short-term findings indicate that the overall size of the stock market does not significantly affect electricity usage. This suggests that achieving the desired energy-saving goals may require policies that account for the influence of stock market on energy demand, rather than excluding this factor. Given these findings, policymakers in GCC countries should take into account the intricate and various effects that stock market development have on energy consumption. Accordingly, to reduce energy consumption, policies should not solely focus on energy demand and income relationships. Instead, policies should encourage improved corporate governance practices that incentivize companies to reduce their energy consumption to improve their financial performance and increase their share prices. This can be achieved by encouraging companies to invest in energy-efficient technologies and reducing their reliance on energy-intensive projects. Additionally, policymakers should consider regulating the stock market to promote environmentally responsible investments and reduce the financing of energy-intensive projects.